Artificial Intelligence in accounting: opportunities, risks, and workforce transformation - Rusli, Ros Syuhada Natasya; Saidi, Noraida (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
AI has revolutionized accounting, increasing the degree of accuracy, efficiency and decision-making ability. Modern financial reporting, auditing, tax compliance and risk management technologies driven by AI predictive analytics, machine learning and robotic process automation. The highest advantages of deploying AI in business include processing transactions promptly and accurately, high-level fraud discovery, and accurate financial forecasts. But the acceleration of artificial intelligence in accounting also comes with ethical troubles, data security, and other dangers while also threatening job loss. This paper investigates the benefits as well as the drawbacks of artificial intelligence related to the accounting profession. By defining traditional accounting functions, it also highlights how AI-powered solutions can eliminate human errors, boost productivity, and offer enhanced financial insights. In addition, it explains the implications for artificial intelligence implementation in the regulatory compliance context, as well as it describes the skills set for accountants and the risks of overreliance on automated systems. Although the application of artificial intelligence can bring about revolutionary changes, the proper use of technology is crucial to avoid the risks of cybersecurity, openness, and bias. This study argues that AI is an enabler for human accountants and thus allows professionals to focus on strategic and advisory work. The accounting industry can navigate the AI based future appropriately by adopting ethical AI practices, spending on the retirement of staff, and ensuring strong cybersecurity.